MANAJEMEN PROGRAM TAHFIDZUL QUR’AN DALAM PENINGKATAN KUANTITAS HAFALAN AL QUR’AN - Mar'atus Sholihah; Edy Muslimin; Yunan Hidayat (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
The Qur'an is the holy book of Muslims which contains many instructions for mankind.In this case, MTSS Qoryatul Qur'an Sukoharjo wants to make the management of the tahfidzul qur'an program in increasing the memorization of female students, so MTSS Qoryatul Qur'an uses tahfidz program management with a block system to achieve the targets. This study aims to determine the management of the tahfidz program with a block system whether it is efficient to increase the quantity of memorization of female students in class VIII.This research is a field research using a descriptive qualitative approach. The subject of this research is santriwarti class VIII MTSS Qoryatul Qur'an Sukoharjo. In collecting data, researchers used observation, interview, and documentation techniquesThe results of this study indicate that the management of the tahfidzul qur'an program in increasing the quantity of memorization of the Qur'an in class VIII of MTSS Qoryatul Qur'an Sukoharjo in 2023/2024 is in accordance with POCCC but in the process of implementation there are several obstacles from the halaqoh guardian and santriwati who are the subject of management. So that the program to increase memorization of the Qur'an in class VIII MTSS Qoryatul Qur'an Sukoharjo has not been achieved optimally.